2012
DOI: 10.1177/0269881111431751
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine augmentation of serotonin reuptake inhibitors in treatment-resistant obsessive–compulsive disorder: a double-blind, placebo-controlled study

Abstract: The present 16-week double-blind, randomized, placebo-controlled trial had the aim to explore the efficacy of lamotrigine add-on pharmacotherapy on clinical symptomatology and cognitive functioning in a sample of patients with treatment-resistant obsessive-compulsive disorder (OCD) receiving serotonin reuptake inhibitors (SRIs). After clinical and neurocognitive assessments, patients were randomly allocated to receive, in a double-blind design, 100 mg/day of lamotrigine or a placebo. A final sample of 33 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 50 publications
1
61
0
Order By: Relevance
“…[16][17][18][19][20] In addition, in at least 1 previous case series, it was reported that some patients with hoarding disorder responded to extended-release methylphenidate. 21 Thus, our report suggests that the treatment of bipolar depression, when present, may help patients with different types of obsessivecompulsive and related disorder symptoms, including hoarding.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] In addition, in at least 1 previous case series, it was reported that some patients with hoarding disorder responded to extended-release methylphenidate. 21 Thus, our report suggests that the treatment of bipolar depression, when present, may help patients with different types of obsessivecompulsive and related disorder symptoms, including hoarding.…”
Section: Discussionmentioning
confidence: 99%
“…Positive results were obtained in a small randomized controlled trial of lamotrigine (Bruno et al, 2012). Randomized placebo controlled trials of topiramate augmentation resulted in a therapeutic effect (reducing compulsions only) in one study (Berlin et al, 2011) whereas another study (Mowla et al, 2010) noted significant improvement in the topiramate as opposed to the placebo group.…”
Section: Combining Ssri and Clomipraminementioning
confidence: 99%
“…There are few RCTs with antiepileptics in OCD, but one [121] suggests that lamotrigine may potentiate the effects of serotonergic reuptake inhibitors in treatment-resistant OCD, possibly due to its glutamatergic effects. A recent guideline recommended SSRI augmentation with lamotrigine or topiramate as one of the options after initial SSRI nonresponse in OCD [111].…”
Section: Newer Antidepressantsmentioning
confidence: 99%